Enhanced butanone chemoresistive sensor utilizing cobalt oxide nanoparticles - Zito, Cecilia A. [UNESP]; Theodoro, Reinaldo S. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Sá, Bruna S.de [UNESP]; Vioto, Gabriel C.N. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2024)
Detection of volatile organic compounds (VOCs), particularly 2-butanone, has become crucial due to their widespread use and associated risks to human health. In this study, we present a novel synthesis method for spinel Co3O4 nanoparticles (NPs) employing a microwave-assisted hydrothermal approach followed by calcination and investigate their efficiency in VOC sensing applications. The Co3O4 NPs exhibit remarkable sensitivity and selectivity towards butanone at relatively low operating temperatures. VOC-sensing experiments reveal an optimal operating temperature of 250 °C, showcasing an advantage over existing sensors. Notably, the sensor exhibits high selectivity for butanone, with signal values 1.6–4.5 times higher than those for other VOCs, including acetaldehyde, ethanol, isopropanol, methanol, acetone, m-xylene, toluene, and benzene. Additionally, the Co3O4 NPs-based sensor demonstrates high sensitivity, detecting concentrations as low as 5 ppm of butanone, with fast response/recovery times of 41/86 s for 200 ppm of butanone and robust long-term stability. These findings underscore the potential of Co3O4 NPs as promising candidates for low-temperature butanone detection, which is essential for environmental and human health monitoring purposes.
Keywords: Cobalt(II,III) oxide; Gas sensor; Low-temperature; Methyl ethyl ketone; p-type